Assessment of the viability of using tertiary treated water for cooling tower circulating water for the open loop of HVAC systems via corrosion test of steel - Ty, Troy Benedict L.
Wastewater reuse is a viable method of conservation of fresh water in lieu of diminishing easily accessible fresh water resources. Tertiary water can be used in a variety of applications that normally demand high volume of potable water. Industrial, agricultural and commercial establishments can use tertiary water for their needs. Exploring these applications can ease pressure on local fresh water resources especially in arid areas as well as areas where fresh water sources are no longer viable. This paper assesses the use of tertiary water in commercial buildings using corrosion as the main criterion. Metal tags were exposed to four different kinds of water sources. Two of the water sources represent classes of tertiary waters as classified by the DENR using Class C and Class D effluent standards. One represented the manufacturer's specifications of water quality and finally the last one was onsite tertiary treated wastewater servicing a commercial center in Metro Manila. The last case was an onsite demonstration of the use tertiary water in cooling towers. The results showed a threefold increase in corrosion rate when using tertiary water in place of the manufacturer's specifications leading to a decrease in equipment lifespan but still within acceptable industry standards with a corrosion rate of 3 to 5 which is classed as good. They had corrosion rates of 3.7361 mpy for Class D, 3.099 mpy for Class C, 3.2593 mpy for the site setup and 0.6332 mpy for the manufacturer's specifications. The corrosion rate was then used to calculate the equipment life considering increased corrosion on its parts. While corrosion is significant, the financial savings from water cost majorly outweighed the loss in equipment's serviceable life with a return in 1.5 years.